The Effect Of Static By Cycle Exercise On Genu Stiffness In Osteoatritis At Pure Muurni Teguh Hospital Medan - Tuty Swarni Sinaga; Jhon Roby Purba; Theresia Anggraeni; AfnizarWahyu (CV. AFDIFAL MAJU BERKAH, 2025)
This community service will seek to establish the effectiveness of career preparation programs for students within the ranks of ABIM to better equip them for both higher education and the workforce. This research used a qualitative approach, incorporating workshops, interviews, and interactive sessions in the course of conducting an evaluation of the students' preparedness for careers. The findings indicated that structured career planning programs enhanced the students' confidence, knowledge about career opportunities, and preparedness to face academic and professional challenges. The study concludes that targeted interventions in career guidance are very necessary for empowering students with the necessary competencies for their future academic and career paths.